1993
DOI: 10.2170/jjphysiol.43.87
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Jaw Reflexes Induced by Incisal and Molar Pressure Stimulation in Relation to Background Levels of Jaw-Clenching Force in Humans.

Abstract: Patterns of jaw reflexes induced by periodontal stimulation were examined in ten adults. Surface electromyograms (EMGs) from the masseter and anterior temporal muscles were recorded when pressure stimulation was applied to either an incisor or a molar. Reflex responses to periodontal pressure stimulation varied, depending on the background levels of jaw-clenching force that preceded stimulation (background clenching force, BCF). At low BCF, excitatory reflexes were elicited from the jaw-closing muscles and jaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…It has been shown that the change from an excitatory reflex to an inhibitory reflex is related to the size of MUs, BGA, or the direction and strength of the mechanical stimulation applied to the teeth (Trulsson and Johansson, 1996; Türker et al, 1997; Yang and Türker, 2001; Brinkworth and Türker, 2005). When axial pressure stimulation was applied to the maxillary molar, an inhibitory reflex occurred in the masseter muscle when the occlusal force was large, while an excitatory reflex was easily evoked when the occlusal force was small (Yamamura et al, 1993). Sowman and Türker (2008) found that the RR of incisor-driven PMR is negatively correlated with the amount of pre-load applied to the incisor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the change from an excitatory reflex to an inhibitory reflex is related to the size of MUs, BGA, or the direction and strength of the mechanical stimulation applied to the teeth (Trulsson and Johansson, 1996; Türker et al, 1997; Yang and Türker, 2001; Brinkworth and Türker, 2005). When axial pressure stimulation was applied to the maxillary molar, an inhibitory reflex occurred in the masseter muscle when the occlusal force was large, while an excitatory reflex was easily evoked when the occlusal force was small (Yamamura et al, 1993). Sowman and Türker (2008) found that the RR of incisor-driven PMR is negatively correlated with the amount of pre-load applied to the incisor.…”
Section: Discussionmentioning
confidence: 99%
“…Since this type of PMR stimulation is known to elicit an excitatory effect on the masseter motoneurons (Yamamura et al, 1993;Taguchii et al, 1995), the effectiveness of other excitatory inputs must have decreased during the PMR stimulation.…”
Section: The Distribution Of Periodontal Inputmentioning
confidence: 99%
“…As tonic stimulation of PMRs induces excitatory effects on the jaw-closer motoneurons (Yamamura et al, 1993;Taguchii et al, 1995), the PMR input to the motoneurons should contribute significantly to their discharge during a voluntary biting task (Morimoto and Nagashima, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal jaw-reflex recordings were carried out by a slight modification of the method described by Yamamura et al (1993). An impression of the maxillary *Yoshida Co., Tokyo, Japan.…”
Section: Periodontai Jaw-reflexmentioning
confidence: 99%
“…In fact, reflex responses to pressure stimuli applied to the periodontium or PDL varies according to the levels of background jaw-clenching force (BCF) prior to stimulation: an excitatory reflex occurs when the BCF is low whereas an inhibitory reflex is elicited hy a high BCF (Yamamura et al 1993). Therefore, measuring the periodontal jaw reflex by a force sensor embedded ivithin a bile block would offer means for a chairside evaluation of a novel occlusal parameter useful in oral rehabilitation.…”
Section: Introductionmentioning
confidence: 99%